2018
DOI: 10.2147/ijnrd.s149877
|View full text |Cite
|
Sign up to set email alerts
|

Pulse versus daily oral Alfacalcidol treatment of secondary hyperparathyroidism in hemodialysis patients: a randomized controlled trial

Abstract: Background: Secondary hyperparathyroidism is a common complication of chronic kidney disease and is managed using vitamin D replacement therapy. Very few studies have examined the effectiveness of pulse alfacalcidol therapy in comparison to daily oral alfacalcidol therapy in suppressing serum parathyroid hormone (PTH) levels in hemodialysis patients. The aim of this randomized controlled trial was to replicate the findings of prior studies comparing effectiveness of pulse oral alfacalcidol therapy versus daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…These findings correlate with a previous study conducted in Japan that suggested a strong association with the hyperparathyroidism because of long duration on dialysis therapy and generalized bone loss [ 27 ]. This is attributed to a combination of factors, including reduction in vitamin D synthesis, hyperphosphatemia, hypocalcemia, and PTH skeletal resistance which will eventually increase the risk of mortality and morbidity as a result of bone disease and fractures [ 11 ]. The hyper activated PTH is considered to deteriorate bone mechanical properties, to rescue the state of hypocalcemia among ESRD patients, on the expense of changing bone structure and reducing bone mass [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings correlate with a previous study conducted in Japan that suggested a strong association with the hyperparathyroidism because of long duration on dialysis therapy and generalized bone loss [ 27 ]. This is attributed to a combination of factors, including reduction in vitamin D synthesis, hyperphosphatemia, hypocalcemia, and PTH skeletal resistance which will eventually increase the risk of mortality and morbidity as a result of bone disease and fractures [ 11 ]. The hyper activated PTH is considered to deteriorate bone mechanical properties, to rescue the state of hypocalcemia among ESRD patients, on the expense of changing bone structure and reducing bone mass [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary hyperparathyroidism is a common complication of CKD and it is attributed to hyperphosphatemia, hypocalcemia, reduced vitamin D synthesis as well as PTH skeletal resistance [ 5 , 10 , 11 ]. The excessive secretion of PTH among renal failure patients results in increased bone turnover [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Causes of SHPT include phosphate retention, calcium and vitamin D reduction, and FGF-23 elevation, as well as decreased expression of CaSR, vitamin D receptor, FGF-23 receptor, and klotho in the parathyroid gland. Moreover, the expression of the parathyroid receptor is reduced by uremic toxins, for example, p-cresyl sulfate and indoxyl which increases cyclic adenosine 3', 5' monophosphate (cAMP) synthesis in the osteoblast [9,13,26]. This cAMP influences skeletal resistance to PTH and eventually osteoporotic fracture [9].…”
Section: Methodsmentioning
confidence: 99%